Orbital masses: a review of CT imaging characteristics - Levanon, Eran; Greenberg, Gahl; Lustig-Barzelay, Yael; Landau-Prat, Daphna; Ben Simon, Guy J. (Frontiers in Ophthalmology, 2025)
Orbital masses include a diverse spectrum of benign, malignant, inflammatory, and vascular lesions in pediatric and adult patients. Accurately diagnosing the type of lesion is critical, as management strategies differ significantly. Advanced imaging is therefore essential, and computed tomography (CT) is central to orbital evaluation. We reviewed the literature to synthesize evidence on CT features across common orbital pathologies and correlated imaging with clinical presentation to emphasize diagnostic relevance. CT characteristics are summarized for vascular lesions (cavernous venous malformation, lymphatic malformation), inflammatory conditions (orbital myositis, dacryoadenitis), benign lesions (dermoid cyst, pleomorphic adenoma), and malignant lesions (lacrimal gland lymphoma, adenoid cystic carcinoma, rhabdomyosarcoma). We present characteristic patterns of location, morphology, enhancement, and bone change, with practical discriminators and common pitfalls to aid differentiation. When used alongside clinical context, CT remains a preferred modality in many clinical settings due to its rapid acquisition, wide availability, and reliable depiction of bone and calcifications. It supports accurate diagnosis and informed management decisions in time-critical settings. This review provides a structured reference for interpreting CT findings across a wide range of orbital disease.